(untitled) (Comprehensive Journal of Science, 2026)
[The aim of this research was to identify the nature of e-government programs and clarify their impact on the governmental accounting system within the administrative work framework. The research reached several results, including: a strong positive correlation (R=0.606), meaning that the governmental accounting system is not isolated from technological developments; rather, it develops proportionally with the increasing reliance on e-government applications. The research recommended the necessity of designing advanced training programs for accountants in government units, focusing on digital accounting information systems and how to deal with relational databases instead of paper records.]